PREPARATION OF POLYMERIC NANOPARTICLES OF ALBUMIN AND IMMOBILIZATION OF THEM WITH THE ANTICANCER DRUG “CYCLOPHOSPHANE” - Yerkeblan M. Tazhbayev; Abdigali A. Bakibaev; Altynarai T.Takibayeva; Tolkyn S. Zhumagalieva; Lyazzat Zh. Zhaparova; Ayaulym A. Agdarbek; Nazgul Zh. Gazizova; Olzhas E. Mukashev; Aizhan M. Tazhibay (Academic Scientific Journal of Chemistry, 2019)
Nanoparticles based on biodegradable and biocompatible polymers allow to attain the targeted drug delivery to the specific organ, without affecting healthy cells of the body and prolonging the therapeutic effect of the drug substance. This study is devoted to the development of the method for the preparation of nanoparticles of human serum albumin (HSA) immobilized with the anticancer drug Cyclophosphamide. Albumin nanoparticles with the sizes of 150-170 nm and narrow particle size distribution (PDI 0.069-0.116) were obtained by coacervation. The yield of nanoparticles is 88.5%. The degree of binding of the drug to polymer nanoparticles was within the range of 54.6% to 92.4%. The drug release was prolonged. After 42 hours 68-77% of the biologically active substance was released from the polymer matrix. It is concluded that the development of HSA-based nanocarrier is promising for the Cyclophosphamide preparation.